Treatment of tuberculosis and optimal dosing schedules. Issue 11 (17th December 2010) - Chang, Kwok Chiu; Leung, Chi Chiu; Grosset, Jacques; Yew, Wing Wai
Abstract : Intermittent tuberculosis treatment regimens have been developed to facilitate treatment supervision. Their efficacy has been substantiated by clinical trials and tuberculosis control programmes, notwithstanding the lack of head-to-head comparison between daily and intermittent regimens. Recently, there has been opposing evidence from observational studies, pharmacokinetic-pharmacodynamic studies and animal models that intermittent treatment increases the risk of relapse, treatment failure or acquired rifamycin resistance, especially among HIV-infected patients. Systematic reviews have been conflicting. PubMed, Ovid MEDLINE and EMBASE were systematically searched for publications in English to evaluate the evidence about dosing schedules and treatment efficacy. Levels of evidence and grades of recommendation were assigned largely according to clinical evidence with reference to the Scottish Intercollegiate Guidelines Network guideline development handbook. A total of 32 articles were included after excluding 331 ineligible articles, 42 non-analytical studies, 22 narrative reviews or expert opinions and 44 articles embedded in systematic reviews. These included 9 systematic reviews, 8 controlled studies, 9 pharmacokinetic-pharmacodynamic studies, 5 mouse studies and 1 article about guinea pig experiments. Findings suggest high levels of evidence for using daily dosing schedules, especially during the initial phase in the presence of cavitation, isoniazid resistance and advanced HIV co-infection, to reduce the risk of treatment failure, recurrence and acquired drug resistance including acquired rifamycin resistance. This review justifies the use of daily schedules in standard tuberculosis treatment regimens (particularly in the initial phase), corroborates prevailing understanding of pharmacokinetics-pharmacodynamics and mycobacterial persisters, and supports exploration of rifapentine-containing regimens in higher dosages and frequency.